2020
DOI: 10.1073/pnas.1922133117
|View full text |Cite
|
Sign up to set email alerts
|

Trinuclear copper biocatalytic center forms an active site of thiocyanate dehydrogenase

Abstract: Biocatalytic copper centers are generally involved in the activation and reduction of dioxygen, with only few exceptions known. Here we report the discovery and characterization of a previously undescribed copper center that forms the active site of a copper-containing enzyme thiocyanate dehydrogenase (suggested EC 1.8.2.7) that was purified from the haloalkaliphilic sulfur-oxidizing bacterium of the genus Thioalkalivibrio ubiquitous in saline alkaline soda lakes. The copper cluster is formed by three copper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
(50 reference statements)
2
27
0
Order By: Relevance
“…Speculatively, it is also possible, where dissolved Cu concentrations were observed to increase slightly towards the end of our experiments, that release of Cu from SCN − -degrading bacterial cells, in stationary and/or death phases, could explain this observation. Previous findings of the incorporation of Cu in one of the main enzymes involved in autotrophic SCN − biodegradation (Tikhonova et al 2020), along with the inhibitory effect of cell-associated Cu (De Schamphelaere et al 2005), would support this speculation.…”
Section: Discussionmentioning
confidence: 84%
“…Speculatively, it is also possible, where dissolved Cu concentrations were observed to increase slightly towards the end of our experiments, that release of Cu from SCN − -degrading bacterial cells, in stationary and/or death phases, could explain this observation. Previous findings of the incorporation of Cu in one of the main enzymes involved in autotrophic SCN − biodegradation (Tikhonova et al 2020), along with the inhibitory effect of cell-associated Cu (De Schamphelaere et al 2005), would support this speculation.…”
Section: Discussionmentioning
confidence: 84%
“…100 mg) in the human body [20]. It works as a cofactor that binds to various metalloenzymes and assists their activation [4,21]. Since it usually exists as cuprous ions [Cu(I)] and cupric ions [Cu(II)], Cu(I/II) can serve as an electron transporter.…”
Section: Cu(i/ii) 21 Cu(i/ii) Distributions In the Nervous Systemmentioning
confidence: 99%
“…We identified a 489-amino acid protein (SCN18_10_11_15_R3_B_scaffold_20_388) that was initially annotated as thiocyanate hydrolase, but the three subunits expected (scnABC of the carbonyl sulfide pathway) were not present. Further analyses (Methods) indicated that the gene encodes thiocyanate desulfurase of the cyanate pathway (Tikhonova et al, 2020). This identification was strongly supported by selection of threading templates using I-TASSER (Yang et al, 2015) as well as by SWISS-MODEL (Waterhouse et al, 2018) (33.7% identity, top match to PDB 5F75, with four Cu ligand sites identified although the GMQE score is below expectation relative to the value expected for experimental structures of similar size) and Phyre2 (Kelley et al, 2015) (template fold library ID c5f30B, thiocyanate desulfurase from Thioalkalivibrio paradoxus) (Figure 4).…”
Section: Predicted Metabolism and Capacity For Scn − Degradationmentioning
confidence: 99%